Understanding the Role of Aldose Reductase in Ocular Inflammation - Yadav, Umesh CS (2010)
Aldose reductase, although identified initially as a glucose-reducing enzyme via polyol pathway, is believed to be an important component of antioxidant defense system as well as a key mediator of oxidative stress-induced molecular signaling. The dual role played by AR has made it a very important enzyme for the regulation of not only the cellular redox state by detoxifying the reactive lipid-aldehydes generated by lipid peroxidation which is crucial in the cellular homeostasis, but also in the regulation of molecular signaling cascade that may regulate oxidative stress-induced cytotoxic events. Search for the new molecular targets to restrain the oxidative stress-induced inflammation has resulted in the identification of AR as an unanticipated mediator of oxidative stress-induced signaling. Although, in last one decade or so AR has been implicated in various inflammation-related disease conditions ranging from diabetes, sepsis, cancer, cardiovascular and airway inflammation, however, a critical evaluation of the clinical efficacy of AR inhibitors awaits a better understanding of the role of AR in regulating inflammation, especially in ocular inflammation.